Banff Histopathological Consensus Criteria for Preimplantation Kidney Biopsies. Issue 1 (22nd July 2016) - Liapis, H.; Gaut, J. P.; Klein, C.; Bagnasco, S.; Kraus, E.; Farris, A. B.; Honsova, E.; Perkowska‐Ptasinska, A.; David, D.; Goldberg, J.; Smith, M.; Mengel, M.; et al.
Abstract : The Banff working group on preimplantation biopsy was established to develop consensus criteria (best practice guidelines) for the interpretation of preimplantation kidney biopsies. Digitally scanned slides were used (i) to evaluate interobserver variability of histopathologic findings, comparing frozen sections with formalin‐fixed, paraffin‐embedded tissue of wedge and needle core biopsies, and (ii) to correlate consensus histopathologic findings with graft outcome in a cohort of biopsies from international medical centers. Intraclass correlations (ICCs) and univariable and multivariable statistical analyses were performed. Good to fair reproducibility was observed in semiquantitative scores for percentage of glomerulosclerosis, arterial intimal fibrosis and interstitial fibrosis on frozen wedge biopsies. Evaluation of frozen wedge and core biopsies was comparable for number of glomeruli, but needle biopsies showed worse ICCs for glomerulosclerosis, interstitial fibrosis and tubular atrophy. A consensus evaluation form is provided to help standardize the reporting of histopathologic lesions in donor biopsies. It should be recognized that histologic parameters may not correlate with graft outcome in studies based on organs deemed to be acceptable after careful clinical assessment. Significant limitations remain in the assessment of implantation biopsies. Abstract : The Banff preimplantation biopsy working group reports the results of histopathological digital evaluation of preimplantation kidney biopsies by expert renal pathologists, provides a consensus form to help standardize reporting of donor biopsies, and reiterates the advantages and limitations of using pathology to predict graft outcomes.